Supply chain risk management model as a differentiating element - Zamudio Pereda, Oscar (2021)
Today, the complexities of the supply chain pose enormous challenges for organizations. This has intensified the need and constant search for resilient management. The risks that threaten it arise unexpectedly and aggressively at any point in the logistics chain and their impact may not always be favorably outweighed by companies. Likewise, those responsible must manage various contingency factors in increasingly competitive environments, this has meant until today the establishment of methods of how to shield the probable disruptions in various  scenarios. However, comprehensive risk management can be an effective approach to address these uncertainties. In this sense, the information developed aims to be useful to various organizations and especially their managers in charge of management, so that they make decisions based on shared and reflective experience, aimed at business competitiveness.